Pengembangan Model Pembelajaran ALBICI dengan Strategi Pembelajaran PDEODE Berbantuan PhET Simulations untuk Meningkatkan Penguasaan Konsep Fisika Peserta Didik SMA - Ramdhani, Izmy Chantika; Sugianto (Universitas Negeri Semarang, 2024)
Regulations of Mendikbudristek RI No. 16 Tahun 2022, In order for the learning process to be effective and efficient, teachers must be able to create an interactive learning atmosphere and actively involve students. The goal of the physics learning process is to master the concept of physics. To improve concept mastery, a learner-centered learning model is needed with media that actively involves students. So the researchers tried to develop an Active Learning Based Interactive Conceptual Instructions (ALBICI) learning model with Predict Discuss Explain Observe Discuss Explain (PDEODE) strategy assisted by PhET Simulations to improve students' mastery of physics concepts. This study aims to determine the feasibility and effectiveness of the developed learning model. The research method used in this study is the research and development (R&D) method with the ADDIE model research design (Analysist, Design, Development, Implementation, Evaluations). This research was conducted at SMA Negeri 1 Sukahaji with class X MIPA 1 as the trial class. The analysis technique to test the feasibility of the product uses expert validity test while to test the effectiveness of the product using N-Gain test and t-test. The product feasibility test showed that the experimental class lesson plan was 94% (very feasible) and the experimental class LKPD was 97% (very feasible). The N-Gain test results in the control class were 0.26 which was classified as low while in the experimental class 0.31 which was classified as moderate. Thus, it can be concluded that the learning model developed is quite effective. The t-test results based on the posttest results of the control and experimental classes obtained a thitung of 2.181 with a ttabel of 2.002. So that thitung < ttabel or it can be concluded that there is a difference in concept mastery between the control and experimental classes.